A carbon-carbon crucible with silicon-carbon-nitrogen oxygen-free coating and a preparation method thereof

By forming a silicon-carbon-nitrogen-free coating on the surface of the carbon-carbon crucible, the mechanical properties and service life problems caused by silicification erosion during the single crystal silicon drawing process of the quartz crucible are solved, and higher anti-silicification corrosion performance and extended service life are achieved.

CN117049896BActive Publication Date: 2025-03-28上海康碳复合材料科技有限公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311139558.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-28
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

During the process of single crystal silicon drawing, existing quartz crucibles have silicified erosion caused by silicon vapor and molten silicon splash, and their mechanical properties and service life are affected.

Method used

A carbon-carbon crucible with a silicon carbon-nitrogen oxygen-free coating is used to form silicon nitride and silicon coatings on the surface of the crucible through vacuum impregnation and ultrasonic spraying technology, and the silicon carbon-nitrogen oxygen-free coating is reacted in situ through high-temperature heat treatment to form a silicon carbon-nitrogen oxygen-free coating.

Benefits of technology

It improves the anti-silicification corrosion performance and surface mechanical properties of carbon-carbon crucibles, extends the service life and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004433668930000101
    Figure BDA0004433668930000101
  • Figure BDA0004433668930000111
    Figure BDA0004433668930000111
Patent Text Reader

Abstract

The present invention belongs to the field of material technology, and specifically relates to a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating and a preparation method thereof. The present invention performs polysilazane solution impregnation treatment on the carbon-carbon crucible substrate, forms a silicon nitride coating on the surface of the carbon-carbon crucible through vacuum heat treatment, and then sprays silicon powder on the inner surface of the carbon-carbon crucible by supersonic spraying to form a silicon coating. Finally, the silicon nitride coating and the silicon coating react through heat treatment to react in situ on the inner surface of the crucible to form a silicon-carbon-nitrogen oxygen-free coating, which has a stronger interlayer bonding force, can effectively seal the carbon-carbon crucible, make its surface denser, prevent silicon liquid from penetrating, prevent silicon vapor from chemically reacting with the carbon-carbon crucible, effectively prevent the carbon-carbon crucible from being corroded and damaged, and play a role in protecting the carbon-carbon crucible. It can effectively improve the high-temperature mechanical properties and anti-siliconization corrosion performance of the carbon-carbon crucible and extend the service life of the carbon-carbon crucible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating and a preparation method thereof. Background Art

[0002] At present, the crucible used in the single crystal silicon pulling furnace is generally made of quartz crucible. However, in recent years, there has been a shortage of high-purity quartz sand raw materials and import restrictions. In addition, the quartz crucible can be used for about 15 days, with a short service life and frequent replacement, which greatly increases the production cost of the enterprise. Moreover, as the size of single crystal silicon continues to increase, the size requirements for thermal field components are also increasing. Carbon-carbon composite materials have become the first choice for thermal field materials for single crystal silicon due to their dimensional stability and excellent mechanical properties. However, in the process of pulling single crystal silicon, the melting of silicon material will produce silicon vapor and molten silicon splashing, causing siliconization erosion of carbon-carbon thermal field materials, and seriously affecting the mechanical properties and service life of carbon-carbon thermal field materials. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating and a preparation method thereof. The carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating prepared by the present invention has high density, high resistance to silicification corrosion and surface mechanical properties, thereby extending the service life.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating, comprising the following steps:

[0006] The carbon-carbon crucible substrate is cyclically vacuum-impregnated in a polynitrogen silane impregnation solution and dried, and then subjected to a first vacuum heat treatment to obtain a carbon-carbon crucible having a silicon nitride coating on the surface;

[0007] After the inner surface of the carbon-carbon crucible with the silicon nitride coating on the surface is subjected to supersonic spraying of the silicon coating, a second vacuum heat treatment is performed to obtain a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating.

[0008] Preferably, the density of the carbon-carbon crucible substrate is 1.65-2.0 g / cm 3 , the opening rate is less than 10%.

[0009] Preferably, the polynitrogen silane impregnation solution comprises liquid polynitrogen silane, silicon nitride powder and silica sol; the solid content of the liquid polynitrogen silane is 75-90%.

[0010] Preferably, the vacuum degree of the vacuum impregnation is 0-0.1 MPa; the number of cycles is 1-5 times; the time of each vacuum impregnation is 10-15 hours, the temperature of each drying is 150-300° C., and the time of each drying is 1-12 hours.

[0011] Preferably, the temperature of the supersonic spraying is 1600-1800°C.

[0012] Preferably, the thickness of the silicon nitride coating is 100-300 μm.

[0013] Preferably, the vacuum degree of the first vacuum heat treatment is 0-0.1 MPa; the temperature of the first vacuum heat treatment is 1800-2200° C.; and the time of the first vacuum heat treatment is 4-12 hours.

[0014] Preferably, the thickness of the silicon coating is 40 to 80 Å.

[0015] Preferably, the vacuum degree of the second vacuum heat treatment is 0-0.1 MPa; the temperature of the second vacuum heat treatment is 1800-2500° C.; and the time of the second vacuum heat treatment is 10-36 hours.

[0016] The present invention also provides a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating prepared by the preparation method described in the above technical solution, comprising a carbon-carbon crucible substrate and a silicon-carbon-nitrogen oxygen-free coating covering the inner surface of the carbon-carbon crucible substrate; the thickness of the silicon-carbon-nitrogen oxygen-free coating is 200 to 600 μm; the density of the inner surface of the carbon-carbon crucible covered with the silicon-carbon-nitrogen oxygen-free coating is 1.85 to 2.15 g / cm 3 The porosity of the inner surface of the carbon-carbon crucible covered with the silicon-carbon-nitrogen oxygen-free coating is <5%.

[0017] The invention provides a method for preparing a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating, comprising the following steps: cyclically vacuum-immersing a carbon-carbon crucible substrate in a polynitrogen silane impregnation solution and drying, and then performing a first vacuum heat treatment to obtain a carbon-carbon crucible with a silicon nitride coating on the surface; supersonic spraying a silicon coating on the inner surface of the carbon-carbon crucible with the silicon nitride coating on the surface, and then performing a second vacuum heat treatment to obtain a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating.

[0018] The present invention performs polysilazane solution impregnation treatment on the carbon-carbon crucible substrate, and then forms a silicon nitride coating on the surface of the carbon-carbon crucible through vacuum heat treatment, and then uses supersonic spraying to spray silicon powder on the inner surface of the carbon-carbon crucible to form a silicon coating. Finally, the silicon nitride coating and the silicon coating react through heat treatment, and react in situ on the inner surface of the crucible to form a silicon-carbon-nitrogen oxygen-free coating. After high temperature, the carbon-carbon crucible, the silicon nitride coating and the three elements of C, N, and Si in the silicon coating undergo bonding reactions to form a silicon-carbon-nitrogen oxygen-free coating. The silicon-carbon-nitrogen oxygen-free coating is obtained through in-situ chemical reaction, and the interlayer bonding force is stronger. The carbon-carbon crucible can be effectively sealed to make its surface denser, prevent silicon liquid from penetrating, prevent silicon vapor from chemically reacting with the carbon-carbon crucible, effectively prevent the carbon-carbon crucible from being corroded and damaged, and play a role in protecting the carbon-carbon crucible. It can effectively improve the high-temperature mechanical properties and anti-siliconization corrosion performance of the carbon-carbon crucible and extend the service life of the carbon-carbon crucible.

[0019] The present invention uses a carbon-carbon crucible covered with a silicon-carbon-nitrogen oxygen-free coating to replace a quartz crucible, which can alleviate the problem of domestic quartz sand shortage, and at the same time can increase the service life of the single crystal silicon pulling crucible and reduce the production cost of the enterprise. The present invention combines polysilazane impregnation and supersonic spraying processes to prepare a high-density carbon-carbon composite material crucible for photovoltaic thermal fields, which has the advantages of simple process, convenient operation, short preparation cycle, low production cost, excellent mechanical properties, strong interlayer bonding force, etc., and provides a practical and effective method for large-scale industrial production. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating, comprising the following steps:

[0021] The carbon-carbon crucible substrate is cyclically vacuum-impregnated in a polynitrogen silane impregnation solution and dried, and then subjected to a first vacuum heat treatment to obtain a carbon-carbon crucible having a silicon nitride coating on the surface;

[0022] After the inner surface of the carbon-carbon crucible with the silicon nitride coating on the surface is subjected to supersonic spraying of the silicon coating, a second vacuum heat treatment is performed to obtain a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating.

[0023] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used in the preparation, and commercially available products known to those skilled in the art can be used.

[0024] The present invention performs a first vacuum heat treatment on a carbon-carbon crucible substrate after cyclic vacuum impregnation in a polynitrogen silane impregnation solution and drying to obtain a carbon-carbon crucible with a silicon nitride coating on the surface.

[0025] In the present invention, the method for preparing the carbon-carbon crucible substrate preferably comprises the following steps:

[0026] The carbon fiber is braided and formed to obtain a carbon fiber crucible preform;

[0027] The carbon fiber crucible preform is subjected to heat treatment under protective gas, and then subjected to rough turning to obtain a finished crucible blank;

[0028] Performing vapor deposition densification on the finished crucible blank to obtain a carbon-carbon crucible blank;

[0029] The carbon-carbon crucible blank is sequentially subjected to impregnation-carbonization densification and finish turning to obtain a carbon-carbon crucible substrate.

[0030] The present invention preferably uses carbon fiber weaving to form a carbon fiber crucible preform. In the present invention, the woven structure is preferably a needle-punched structure; the woven forming is preferably achieved by alternately stacking and needle-punching non-woven fabric and ultra-thin mesh tires, and bidirectional penetration of Z-direction carbon fiber.

[0031] After obtaining the carbon fiber crucible preform, the present invention preferably performs heat treatment on the carbon fiber crucible preform under protective gas.

[0032] In the present invention, the protective gas is preferably argon; the purity of the argon is preferably 99.99-99.999%, more preferably 99.999%; the temperature of the heat treatment is preferably 1800-2300°C, more preferably 1900-2000°C, the insulation time is preferably 1-4h, more preferably 2-3h, and the heating rate to the heat treatment temperature is preferably 80-120°C / h, more preferably 90-100°C / h.

[0033] During the heat treatment process, the carbon fiber crucible preform formed by weaving carbon fibers is hardened into shape.

[0034] After the heat treatment, the present invention preferably prefabricates the heat-treated carbon fiber crucible and performs rough turning to obtain a finished crucible blank.

[0035] The present invention has no special limitation on the rough turning. The rough turning well known in the art can be used to obtain a crucible blank of a qualified size according to the drawing.

[0036] After obtaining the finished crucible blank, the present invention preferably performs vapor deposition densification on the finished crucible blank to obtain a carbon-carbon crucible blank.

[0037] In the present invention, the equipment used for the vapor deposition densification is preferably a CVD vapor deposition furnace; the carbon source gas used for the vapor deposition densification is preferably methane; the flow rate of the methane is preferably 2 to 20 m 3 / h, more preferably 5 to 10 m 3 / h; the temperature of the vapor deposition densification is preferably 1000-1200°C, more preferably 1000-1100°C, the time is preferably 100-300h, more preferably 150-200h, and the pressure is preferably 10-100kPa, more preferably 20-80kPa; the heating rate to the temperature required for the vapor deposition densification is preferably 40-80°C / h, more preferably 50-60°C / h; the density of the carbon-carbon crucible blank obtained by the vapor deposition densification is preferably 1.3-1.5g / cm 3 , more preferably 1.4 to 1.5 g / cm 3 .

[0038] In the present invention, the vapor deposition densification is preferably: the finished crucible blank is assembled into a tooling set, and a CVD vapor deposition furnace is used to perform vapor deposition densification.

[0039] The present invention uses vapor deposition densification to initially densify the finished crucible blank, which can maximize the connectivity of the open pores, is conducive to shortening the subsequent resin carbon densification cycle, quickly reaching a predetermined volume density, greatly shortening the preparation cycle, and reducing production costs.

[0040] After obtaining the carbon-carbon crucible blank, the present invention preferably performs impregnation-carbonization densification and finish turning on the carbon-carbon crucible blank in sequence to obtain a carbon-carbon crucible substrate.

[0041] In the present invention, the impregnation-carbonization densification is preferably to impregnate the carbon-carbon crucible blank with phenolic resin, and obtain a carbon-carbon crucible finished blank after cross-linking, curing and high-temperature carbonization.

[0042] In the present invention, the phenolic resin is preferably a phenolic resin emulsion; the solid content of the phenolic resin emulsion is preferably 55-80%, more preferably 60-70%; the impregnation pressure is preferably 1-4MPa, more preferably 2-3MPa; the impregnation time is preferably 1-6h, more preferably 3-5h; the cross-linking curing temperature is preferably 100-200°C, more preferably 120-180°C; the cross-linking curing pressure is preferably 1-3MPa, more preferably 2MPa; the cross-linking curing insulation time is preferably 2-4h, more preferably 3h; the high temperature carbonization temperature is preferably 600-1800°C, more preferably 800-1200°C; the high temperature carbonization insulation time is preferably 10-48h, more preferably 36h. The present invention does not specifically limit the amount of the phenolic resin, as long as it can completely immerse the carbon-carbon crucible blank.

[0043] After obtaining the carbon-carbon crucible finished blank, the present invention preferably performs finish turning on the carbon-carbon crucible finished blank to obtain a carbon-carbon crucible substrate.

[0044] In the present invention, the fine turning preferably comprises: grinding the inner surface and the outer surface of the carbon-carbon crucible finished blank until the surface is flat, smooth and free of residue.

[0045] The present invention directly performs precision turning on the inner and outer surfaces of the carbon-carbon crucible finished blank, so that the internal pores are exposed to the inner and outer surfaces to the maximum extent, which is beneficial to the next step.

[0046] In the present invention, the density of the carbon-carbon crucible substrate is preferably 1.65 to 2.0 g / cm 3 , more preferably 1.8 to 2.0 g / cm 3 The open porosity is preferably less than 10%, more preferably 1 to 5%.

[0047] In the present invention, the polynitrogen silane impregnation liquid comprises liquid polynitrogen silane, silicon nitride powder and silica sol; the solid content of the liquid polynitrogen silane is preferably 75-90%, more preferably 80-85%; the mass ratio of the liquid polynitrogen silane, silicon nitride powder and silica sol is preferably 100:(10-20):(5-10), more preferably 100:15:5; the purity of the silicon nitride powder is preferably 99.999%, and the particle size is preferably 10-100 μm, more preferably 20-50 μm; the solid content of the silica sol is preferably 60-80%, more preferably 65-75%; the solvent used for the silica sol is preferably xylene. The present invention does not specifically limit the amount of the polynitrogen silane impregnation liquid, as long as it can completely immerse the carbon-carbon crucible substrate.

[0048] In the present invention, the vacuum degree of the vacuum impregnation is preferably 0-0.1 MPa, more preferably 0.1 MPa; the number of cycles is preferably 1-5 times, more preferably 2-3 times; the time of each vacuum impregnation is preferably 10-15 hours, more preferably 10-12 hours, the temperature of each drying is preferably 150-300°C, more preferably 180-250°C, and the time of each drying is preferably 1-12 hours, more preferably 6-8 hours.

[0049] In the present invention, the vacuum degree of the first vacuum heat treatment is preferably 0-0.1 MPa, more preferably 0.1 MPa; the temperature of the first vacuum heat treatment is preferably 1800-2200°C, more preferably 1900-2000°C; the time of the first vacuum heat treatment is preferably 4-12h, more preferably 8-12h; the heating rate to the first vacuum heat treatment is preferably 80-120°C / h, more preferably 90-100°C / h.

[0050] The main component of the impregnation liquid is polysilazane. During the vacuum heat treatment process, polysilazane is cracked at high temperature to generate silicon nitride.

[0051] In the present invention, the thickness of the silicon nitride coating is preferably 100 to 300 μm, more preferably 100 to 200 μm.

[0052] The present invention ensures coating effect by repeated dipping and drying.

[0053] After obtaining the carbon-carbon crucible with the silicon nitride coating on the surface, the present invention performs supersonic spraying of the silicon coating on the inner surface of the carbon-carbon crucible with the silicon nitride coating on the surface.

[0054] In the present invention, the purity of the silicon powder used for the supersonic spraying silicon coating is preferably ≥99.999%, more preferably 99.999%, and the particle size is preferably 10-100 μm, more preferably 10-50 μm; the temperature of the supersonic spraying is preferably 1600-1800°C, more preferably 1700-1800°C.

[0055] In the present invention, the thickness of the silicon coating is preferably 40 to 80 Å, more preferably 50 to 60 Å.

[0056] Before the second vacuum heat treatment, the present invention preferably further comprises: placing the sprayed carbon-carbon crucible obtained by the supersonic spraying in a dry environment, and cooling for 6 to 10 hours, more preferably 7 to 8 hours.

[0057] After the supersonic spraying of the silicon coating, the present invention performs a second vacuum heat treatment on the carbon-carbon crucible having the silicon nitride coating on the surface after the supersonic spraying of the silicon coating to obtain a carbon-carbon crucible having a silicon-carbon-nitrogen oxygen-free coating.

[0058] In the present invention, the vacuum degree of the second vacuum heat treatment is preferably 0-0.1 MPa, more preferably 0.1 MPa; the temperature of the second vacuum heat treatment is preferably 1800-2500°C, more preferably 2000-2200°C; the time of the second vacuum heat treatment is preferably 10-36h, more preferably 24-36h; the heating rate to the second vacuum heat treatment is preferably 80-120°C / h, more preferably 90-100°C / h.

[0059] Through vacuum heat treatment, the silicon nitride coating and silicon coating on the inner surface of the carbon-carbon crucible react in situ to form a silicon-carbon-nitrogen oxygen-free coating, thereby improving the siliconization corrosion resistance and surface mechanical properties of the carbon-carbon crucible.

[0060] The present invention also provides a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating prepared by the preparation method described in the above technical solution, comprising a carbon-carbon crucible substrate and a silicon-carbon-nitrogen oxygen-free coating covering the inner surface of the carbon-carbon crucible substrate.

[0061] In the present invention, the thickness of the silicon carbon nitrogen oxygen-free coating is 200 to 600 μm, preferably 200 to 400 μm; the density of the inner surface of the carbon-carbon crucible covered with the silicon carbon nitrogen oxygen-free coating is 1.85 to 2.15 g / cm 3 , preferably 1.9 to 2.15 g / cm 3 The porosity of the inner surface of the carbon-carbon crucible covered with the silicon-carbon-nitrogen oxygen-free coating is less than 5%, preferably 1 to 3.5%.

[0062] In the present invention, the service life of the carbon-carbon crucible with the silicon-carbon-nitrogen oxygen-free coating is preferably 6 to 12 months, more preferably 8 to 10 months.

[0063] The silicon-carbon-nitrogen oxygen-free coating prepared by the present invention can effectively seal the carbon-carbon crucible, making its surface denser, preventing silicon liquid from penetrating, preventing silicon vapor from chemically reacting with the carbon-carbon crucible, effectively preventing the carbon-carbon crucible from being corroded and damaged, and effectively improving the high-temperature mechanical properties and anti-siliconization corrosion properties of the carbon-carbon crucible, and extending the service life of the carbon-carbon crucible. The high-density carbon-carbon crucible covered with a high-density silicon-carbon-nitrogen oxygen-free coating provided by the present invention meets the use requirements of the stress-bearing core structure of the carbon-carbon crucible of a single crystal silicon vertical pulling furnace for photovoltaic thermal fields, and the service life cycle can reach 6 to 12 months.

[0064] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0065] Example 1

[0066] (1) Preparation of carbon-carbon crucible substrate

[0067] The carbon fiber crucible preform is formed by weaving carbon fiber to obtain a carbon fiber crucible preform, the woven structure is a needle-punched structure, and the specific weaving and forming is to use non-woven cloth and ultra-thin mesh tires to alternately stack and needle-punch, and use Z-direction carbon fiber to penetrate in both directions; the obtained carbon fiber crucible preform is placed in a high-temperature furnace and heated to 2000°C at 100°C / h for 3h under the protection of argon gas with a purity of 99.99%, and then roughly turned to obtain a crucible finished blank of qualified size according to the drawing; the crucible finished blank is assembled into a tooling set, and a CVD vapor deposition furnace is used for vapor deposition densification, and the carbon source gas used for vapor deposition densification is a gas with a flow rate of 10m 3 / h of methane, the temperature of vapor deposition densification is 1000°C, the time is 200h, the pressure is 20kPa, the heating rate to the temperature required for vapor deposition densification is 60°C / h, and the density obtained is 1.42g / cm 3The carbon-carbon crucible blank was vacuum-pressure impregnated in phenolic resin (emulsion with a solid content of 70%) at a pressure of 2 MPa for 6 h, then cross-linked and cured at 1000 ° C and 2 MPa for 3 h, then carbonized in a carbonization furnace at a high temperature of 1200 ° C for 36 h, and its inner and outer surfaces were polished until the surface was smooth and free of residue, and a density of 1.82 g / cm was obtained. 3 Carbon-carbon crucible substrate;

[0068] (2) Polysilazane impregnation

[0069] The carbon-carbon crucible substrate is immersed in a polynitrogen silane impregnation solution (including liquid polynitrogen silane (solid content of 85%) with a mass ratio of 100:15:5), silicon nitride powder (purity of 99.999%, particle size of 20 μm) and silica sol (solid content of 75%, solvent is xylene) by a PIP process, evacuated to a vacuum degree of 0.1 MPa for immersion for 10 hours, dried at 180° C. for 8 hours, and after three cycles, heated to 2000° C. at a rate of 100° C. / min in a vacuum environment (vacuum degree of 0.1 MPa) for heat treatment for 12 hours to obtain a carbon-carbon crucible with a silicon nitride coating (100 μm) on the surface;

[0070] (3) Ultrasonic spraying silicon coating

[0071] Silicon powder with a particle size of 50 μm and a purity of 99.999% was taken and the inner surface of a carbon-carbon crucible with a silicon nitride coating on the surface was subjected to overall ultrasonic spraying at a spraying temperature of 1800° C. for a spraying time of 4 h. After cooling in a dry environment for 8 h, a silicon coating with a thickness of 40 filaments was formed to obtain a carbon-carbon crucible with an inner SiN / Si composite coating.

[0072] (4) Vacuum heat treatment

[0073] A carbon-carbon crucible coated with a SiN / Si composite coating was placed in a high-temperature furnace and heated to 2200°C at a rate of 100°C / min for heat treatment for 36 hours in a vacuum environment (vacuum degree of 0.1 MPa). The composite coating reacted with the surface of the carbon-carbon crucible in situ to form a silicon-carbon-nitrogen oxygen-free coating, thereby obtaining a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating (200 μm).

[0074] Example 2

[0075] (1) Preparation of carbon-carbon crucible substrate

[0076] The carbon fiber crucible preform is formed by weaving carbon fiber to obtain a carbon fiber crucible preform, the woven structure is a needle-punched structure, and the specific weaving and forming is to use non-woven cloth and ultra-thin mesh tires to alternately stack and needle-punch, and use Z-direction carbon fiber to penetrate in both directions; the obtained carbon fiber crucible preform is placed in a high-temperature furnace under the protection of argon gas with a purity of 99.99% and heated at 100°C / h to 2000°C for 3h, and then rough-turned to obtain a crucible finished blank of qualified size according to the drawing; the crucible finished blank is assembled into a tooling set, and a CVD vapor deposition furnace is used for vapor deposition densification, and the carbon source gas used for vapor deposition densification is a gas with a flow rate of 10m 3 / h of methane, the temperature of vapor deposition densification is 1000°C, the time is 200h, the pressure is 20kPa, the heating rate to the temperature required for vapor deposition densification is 60°C / h, and the density obtained is 1.44g / cm 3 The carbon-carbon crucible blank was vacuum-pressure impregnated in phenolic resin (emulsion with a solid content of 70%) at a pressure of 2 MPa for 6 h, then cross-linked and cured at 1000 ° C and 2 MPa for 3 h, then carbonized in a carbonization furnace at a high temperature of 1200 ° C for 36 h, and its inner and outer surfaces were polished until the surface was smooth and free of residue, and the density was 1.86 g / cm 3 Carbon-carbon crucible substrate;

[0077] (2) Polysilazane impregnation

[0078] The carbon-carbon crucible substrate is immersed in a polynitrogen silane impregnation solution (including liquid polynitrogen silane (solid content of 85%) with a mass ratio of 100:15:5), silicon nitride powder (purity of 99.999%, particle size of 40 μm) and silica sol (solid content of 75%, solvent is xylene) by a PIP process, evacuated to a vacuum degree of 0.1 MPa for immersion for 10 hours, dried at 180° C. for 8 hours, and after three cycles, heated to 2000° C. at a rate of 100° C. / min in a vacuum environment (vacuum degree of 0.1 MPa) for heat treatment for 12 hours to obtain a carbon-carbon crucible with a silicon nitride coating (150 μm) on the surface;

[0079] (3) Ultrasonic spraying silicon coating

[0080] Silicon powder with a particle size of 50 μm and a purity of 99.999% was taken and the inner surface of a carbon-carbon crucible with a silicon nitride coating on the surface was subjected to overall ultrasonic spraying at a spraying temperature of 1800° C. for a spraying time of 6 h. After cooling in a dry environment for 8 h, a silicon coating with a thickness of 50 filaments was formed to obtain a carbon-carbon crucible with an inner SiN / Si composite coating.

[0081] (4) Vacuum heat treatment

[0082] A carbon-carbon crucible coated with a SiN / Si composite coating was placed in a high-temperature furnace and heated to 2200°C at a rate of 100°C / min for heat treatment for 36 hours in a vacuum environment (vacuum degree of 0.1 MPa). The composite coating reacted with the surface of the carbon-carbon crucible in situ to form a silicon-carbon-nitrogen oxygen-free coating, thereby obtaining a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating (300 μm).

[0083] Example 3

[0084] (1) Preparation of carbon-carbon crucible substrate

[0085] The carbon fiber crucible preform is formed by weaving carbon fiber to obtain a carbon fiber crucible preform, the woven structure is a needle-punched structure, and the specific weaving and forming is to use non-woven cloth and ultra-thin mesh tires to alternately stack and needle-punch, and use Z-direction carbon fiber to penetrate in both directions; the obtained carbon fiber crucible preform is placed in a high-temperature furnace under the protection of argon gas with a purity of 99.99% and heated at 100°C / h to 2000°C for 3h, and then rough-turned to obtain a crucible finished blank of qualified size according to the drawing; the crucible finished blank is assembled into a tooling set, and a CVD vapor deposition furnace is used for vapor deposition densification, and the carbon source gas used for vapor deposition densification is a gas with a flow rate of 10m 3 / h of methane, the temperature of vapor deposition densification is 1000°C, the time is 200h, and the pressure is 20kPa. More preferably, the heating rate to the temperature required for vapor deposition densification is 60°C / h, and the overall density is 1.42g / cm 3 The carbon-carbon crucible blank was vacuum-pressure impregnated in phenolic resin (emulsion with a solid content of 70%) at a pressure of 2 MPa for 6 h, then cross-linked and cured at 1000 ° C and 2 MPa for 3 h, then carbonized in a carbonization furnace at a high temperature of 1200 ° C for 36 h, and its inner and outer surfaces were polished until the surface was smooth and free of residue, and a density of 1.85 g / cm was obtained. 3 High-density carbon-carbon crucible substrate;

[0086] (2) Polysilazane impregnation

[0087] The carbon-carbon crucible substrate is immersed in a polynitrogen silane impregnation solution (including liquid polynitrogen silane (solid content of 85%) with a mass ratio of 100:15:5), silicon nitride powder (purity of 99.999%, particle size of 60 μm) and silica sol (solid content of 75%, solvent is xylene) through a PIP process, evacuated to a vacuum degree of 0.1 MPa for immersion for 10 hours, dried at 180° C. for 8 hours, and after three cycles, heated to 2000° C. at a rate of 100° C. / min in a vacuum environment (vacuum degree of 0.1 MPa) for heat treatment for 12 hours to obtain a carbon-carbon crucible with a silicon nitride coating (200 μm) on the surface;

[0088] (3) Ultrasonic spraying silicon coating

[0089] Silicon powder with a particle size of 50 μm and a purity of 99.999% was used for overall ultrasonic spraying of the inner surface of a carbon-carbon crucible with a silicon nitride coating on the surface. The spraying temperature was 1800° C. and the spraying time was 8 h. After cooling in a dry environment for 8 h, a silicon coating with a thickness of 60 filaments was formed to obtain a carbon-carbon crucible with an inner SiN / Si composite coating.

[0090] (4) Vacuum heat treatment

[0091] A carbon-carbon crucible coated with a SiN / Si composite coating was placed in a high-temperature furnace and heated to 2200°C at a rate of 100°C / min for heat treatment for 36 hours in a vacuum environment (vacuum degree of 0.1 MPa). The composite coating reacted with the surface of the carbon-carbon crucible in situ to form a silicon-carbon-nitrogen oxygen-free coating, thereby obtaining a carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating (400 μm).

[0092] Performance Testing

[0093] (1) The porosity and density of the carbon-carbon crucible with silicon-carbon-nitrogen oxygen-free coating obtained in Examples 1 to 3 were tested. The results are shown in Table 1.

[0094] Table 1 Density and porosity of the composite crucibles obtained in Examples 1 to 3

[0095]

[0096]

[0097] It can be seen from Table 1 that the carbon-carbon crucible with silicon-carbon-nitrogen oxygen-free coating prepared by the present invention has the characteristics of high density, low open porosity and high surface density compared with the carbon-carbon crucibles on the market. Therefore, it can better isolate the molten silicon when pulling the single crystal, protect the silicon material and prevent the silicon material from leaking. It can also ensure that the crucible is not corroded by the silicon material, thereby extending the service life of the crucible.

[0098] (2) The performance of the carbon-carbon crucible with silicon-carbon-nitrogen oxygen-free coating obtained in Examples 1 to 3 was tested. At the same time, the carbon-carbon crucible with silicon-carbon-nitrogen oxygen-free coating obtained in Examples 1 to 3 was applied to the pulling of single crystal silicon to test its service life. A traditional quartz crucible was used as a control. The results are shown in Table 2.

[0099] Table 2 Performance test results of carbon-carbon crucibles with silicon-carbon-nitrogen oxygen-free coatings obtained in Examples 1 to 3

[0100] Performance Indicators Commercially available quartz crucible Example 1 Example 2 Example 3 Maximum operating temperature (℃) 1650 2600 2600 2600 Compressive strength(MPa) 55~100 167 172 183 Flexural strength(MPa) 30~50 271 278 281 Thermal conductivity (W / m·K) 0.6-1.7 432 433 432

[0101] It can be seen from Table 2 that, compared with traditional quartz crucibles, the carbon-carbon material used in the carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating prepared by the present invention has natural advantages, a higher maximum operating temperature, good density, high strength, and good thermal conductivity. Therefore, the carbon-carbon crucible with a silicon-carbon-nitrogen oxygen-free coating prepared by the present invention has lower energy consumption and a longer service life, and can better avoid the problem of failure in pulling single crystals due to high-temperature deformation of the quartz crucible.

[0102] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-carbon crucible having a silicon-carbon-nitrogen oxygen-free coating, characterized in that: The following steps are involved: The carbon-carbon crucible substrate is cyclically vacuum-impregnated in a polynitrogen silane impregnation solution and dried, and then subjected to a first vacuum heat treatment to obtain a carbon-carbon crucible having a silicon nitride coating on the surface; The polynitrogen silane impregnation solution comprises liquid polynitrogen silane, silicon nitride powder and silica sol; the solid content of the liquid polynitrogen silane is 75-90%; the mass ratio of the liquid polynitrogen silane, silicon nitride powder and silica sol is 100:(10-20):(5-10); the vacuum degree of the vacuum impregnation is 0-0.1MPa; the number of cycles is 1-5 times; the time of each vacuum impregnation is 10-15h, the temperature of each drying is 150-300°C, and the time of each drying is 1-12h; the vacuum degree of the first vacuum heat treatment is 0-0.1MPa; the temperature of the first vacuum heat treatment is 1800-2200°C; the time of the first vacuum heat treatment is 4-12h; After supersonic spraying of a silicon coating on the inner surface of the carbon-carbon crucible having a silicon nitride coating on the surface, a second vacuum heat treatment is performed to obtain a carbon-carbon crucible having a silicon-carbon-nitrogen oxygen-free coating; The temperature of the supersonic spraying is 1600-1800°C; the thickness of the silicon coating is 40-80 microns; The vacuum degree of the second vacuum heat treatment is 0-0.1 MPa; the temperature of the second vacuum heat treatment is 1800-2500° C.; and the time of the second vacuum heat treatment is 10-36 hours.

2. The preparation method according to claim 1, characterized in that: The density of the carbon-carbon crucible substrate is 1.65-2.0 g / cm 3 , the opening rate is less than 10%.

3. The preparation method according to claim 1, characterized in that: The thickness of the silicon nitride coating is 100-300 μm.

4. The carbon-carbon crucible with silicon-carbon-nitrogen oxygen-free coating prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The invention comprises a carbon-carbon crucible substrate and a silicon-carbon-nitrogen oxygen-free coating covering the inner surface of the carbon-carbon crucible substrate; the thickness of the silicon-carbon-nitrogen oxygen-free coating is 200 to 600 μm; the density of the inner surface of the carbon-carbon crucible covered with the silicon-carbon-nitrogen oxygen-free coating is 1.85 to 2.15 g / cm 3 The porosity of the inner surface of the carbon-carbon crucible covered with the silicon-carbon-nitrogen oxygen-free coating is <5%.

Citation Information

Patent Citations

  • Composite coating carbon / carbon composite material crucible and preparation method thereof

    CN103553711A

  • Production process of high-purity free-spraying crucible

    CN108585535A

  • High-temperature-resistant composite coating and preparation method thereof

    CN112573943A